Pencitraan Penyakit Metabolik Tulang dengan Modalitas Kedokteran Nuklir - Sri Puspa Handayani; Erwin Affandi Soeriadi (Syntax Corporation Indonesia, 2021)
Metabolic bone disease is a group of disorders associated with disturbances in changes in calcium levels and phosphorus homeostasis, which occur frequently but are difficult to distinguish based on history, physical examination and imaging studies. Osteoporosis is one that often occurs, which often occurs in women who have a higher risk of osteoporosis (21.7%) than men (14.8%). Clinically, metabolic bone disease is often found in patients with fractures which are the main complications of this disease. The modalities used include plain radiography or even computed tomography (CT) and Magnetic Resonance Imaging (MRI), but currently Bone scan (bone fingerprint) is an examination that can be used to detect, is an imaging technique capable of high resolution in a long time. short (acquisition of whole body or specific parts of bone), relatively low dose, sensitivity and specificity for detecting lesions as a result of tomographic data and is an option in routine examinations in Nuclear Medicine. In this article, we will thoroughly explain the various manifestations in the form of peculiarities of the uptake picture of metabolic disease in bone using bone scan (bone fingerprint) examination using the literature study method or literature review as well as conducting article inclusion and article review. These articles can be in the form of research, systematic reviews or case reports. The places where the research was carried out from these articles all came from abroad, on the continents of Asia, Europe, and America.